The Predictive Value of Decisive and Soft Ultrasound Criteria for Ectopic Pregnancy Identification in 321 Preoperative Cases - Pape, Janna; Bajka, Anahita; Strutas, Deivis; Burkhardt, Tilo; Imesch, Patrick; Fink, Daniel; Samartzis, Eleftherios Pierre; Bajka, Michael (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To define the predictive value of morphological types (MTs) and further criteria in diagnosing ectopic pregnancy (ECP) by transvaginal sonography (TVS) prior to operative confirmation and treatment.Materials and Methods Retrospective cohort analysis of 321 consecutive patients with suspected ECP who were advised to undergo operation.Results ECP was investigated by TVS in all 321 patients. Application of the five selected MTs (blob sign, bagel sign, yolk sac, embryo, heart action) resulted in 85 % of cases receiving a conclusive diagnosis and 12 % receiving a presumed ECP diagnosis. 3 % remained nondiagnostic due to large or multiple ovarian cysts, large myoma, extended hemoperitoneum, or severe pain. ECP diagnosis was confirmed intraoperatively in 97 % of cases and was otherwise (3 %) immediately followed by curettage (CUR). The assessment of free fluid by TVS was achieved in most cases and correlated significantly with free blood. In the majority of cases, free blood was not bound to transmural ECP rupture. Histology confirmed the ECP diagnosis directly or by exclusion in 99 % of cases. Three cases of tubal ECP were diagnosed by TVS but not confirmed by LSC (1 %) and, finally, histology from CUR proved miscarriage (false-positive rate 1 %).Conclusion We confirm the high accuracy of TVS diagnosis of ECP relying on five clearly different MTs, independent of its location. The blob and bagel sign emerged as important types (75 % of all ECPs). Histology from CUR was needed when ECP could not be visualized in LSC. Assessment of free fluid was essential and accurate in predicting free blood.
Keywords: transvaginal sonography; blob sign; bagel sign; laparoscopy; ectopic pregnancy